Case Report: Clinicopathological Analysis of Minute Pulmonary Meningothelial-Like Nodules: Report of 7 Cases - Wang, Ying-xia; Lei, Zi; Yang, Man; Wang, Zhi-yuan; Zhang, Xuan; Pan, Guo-qing (Frontiers in Oncology, 2022)
Objective To investigate the clinical manifestations, radiologic features, pathological features, and immunophenotype of minute pulmonary meningothelial-like nodules (MPMNs). Method This is a retrospective observational study. We collected the clinical data of 7 cases of MPMNs, and performed comprehensive characterization using a combination of clinical, morphological, radiologic and immunohistochemical assessments. Results Of the 7 cases of MPMNs, 6 were female and 1 was male. The median age was 55 years. All MPMNs were multiple in lung with the size from 0,01 to 0,5cm. Chest CT examination showed ground-glass attenuation or solid nodules. Four cases were concomitant with carcinoma and/or pneumonia, and 3 cases occured alone. Four of the 7 patients had no obvious symptoms; 3 patients had chest pain or cough or shortness of breath or hemoptysis. Multiple white nodules were found macroscopically, and the diseased cells grew along the alveolar septum, with relatively normal morphology, rich cytoplasm, unclear cell boundary, and uniform nucleus with delicate chromatin and wihtout atypia; and the diseased cells showed nest or whorls distribution. EMA, PR, CD56 and vimentin were positive in all cases by immunohistochemistry. Conclusions MPMNs are rare benign lesions in the lung, often multiple, usually less than 0.5cm in diameter, most of which have no obvious clinical symptoms. MPMNs are often found by chest CT, and occur independently or concomitant with other lesions. The positive immunohistochemical staining of EMA, PR, CD56, vimentin supports the diagnosis.